Endagered an investigative documentary on the factors that led to journalist assaults in the Philippines - Ardillos, Faith
This qualitative study was conducted to identify and investigative the factors that led to journalist assaults in the Philippines and to present the result of the investigation through a creative output in a form of an investigative documentary. The objectives of the study are answered through interviews with two long-serving journalists and six experts who have knowledge about journalist assaults, media laws and policies, and the Philippine media landscape. Results of this study showed that as journalists function as watchdogs of the government and of the society, the issues they covered made them as primary target of assaults. Since Philippines is a democratic country, these reported assaults pose threats to freedom of the press and of expression. The continuous case of assaults create a chilling effect to some who eventually resort to self-censorship but these assaults also affect some journalists to be more critical and vigilant in reporting about the significant issues in the society like graft and corruption.